Pronominal variation and layers in grammaticalization: the enclitic forms -ello and -lo in the Italo-Romance dialect of Lizzano in Belvedere - Cappellaro, C (Pacini Editore SpA, 2020)
This study investigates the rare phenomenon of the co-occurrence (in Lizzanese, an Italo-Romance dialect spoken in the Tuscan-Emilian Apennines) of two types of enclitic pronoun in interrogative contexts: the unstressed monosyllabic forms -lo (3sg.m)/-la (3sg.f) and the stressed disyllabic forms -ello (3sg.m)/-ella (3sg.f). The coexistence of -lo and -ello is analysed as an instance of ‘layering’ (Hopper 1991) and it is claimed that a peculiar characteristic of Lizzanese historical phonology, the preservation of geminate consonants in posttonic contexts, played a crucial role in the emergence of layering. Moreover, following Loporcaro 2012, this study claims that -ello should be analysed as a syntactic clitic and -lo as a syntactic-and-phonological clitic and that these two clitic categories should be assigned distinct positions in a more refined and enriched cline of grammaticality.